2022
DOI: 10.11648/j.edu.20221102.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between School Autonomy and Students’ Academic Achievement in Government Secondary Schools in East Hararghe Zone, Oromia Regional State, Ethiopia

Abstract: The aim of school autonomy is to improve the education quality by independence and flexibility in managing existing resources. Regardless of this trend, amazingly little is known about how schools use autonomy in practice, and there were many controversies regarding the relationship between school autonomy and students' academic achievement. Therefore, the purpose of this study was to examine the magnitude of relationship between the areas of school autonomy and students' academic achievement in the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…They further suggested that the availability of adequate facilities play a decisive role to face the ECE challenges. Another research study (Hailu and Biyabeyen 2014) also positively support the research finding of our study that facilities are beneficial to teachers for the implementation of early childhood education. The current study's findings illustrate that curriculum of ECE is implemented satisfactorily in public primary schools.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They further suggested that the availability of adequate facilities play a decisive role to face the ECE challenges. Another research study (Hailu and Biyabeyen 2014) also positively support the research finding of our study that facilities are beneficial to teachers for the implementation of early childhood education. The current study's findings illustrate that curriculum of ECE is implemented satisfactorily in public primary schools.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…"equipment, classroom facilities, furniture, toilet, ICT, library and laboratory materials and others". It aids towards a vital job to efficiently execute an educating and learning development (Hailu & Biyabeyen, 2014). Buckley, Schneider, and Shang (2004) described that school facilities empower the educator to achieve his/her assignment too and help the students to learn and develop (Chepkonga, 2017).…”
Section: Early Childhood Curriculum Implementationmentioning
confidence: 99%